Campaña audiovisual “artistas” - Palau, Ingrid (2010)
The lack of dissemination of cultural integration projects, aimed at children and young specialists, is lacking in the city of Guayaquil, thus affecting their development, not only because the letter must reach the foundations but also to families who are the form a partnership which seeks to include them. That's why we created in 2009 the campaign "Artist", an audiovisual production a social character, whose role is to disseminate a conceptual theme based on cultural integration for disabled children in the city of Guayaquil. The purpose of the "Artists" is a massive awareness to all individuals and organizations responsible for ensuring the acceptance of special children who live in our city. Likewise, the economic expectations of the campaign will be based on return auspices of commercial productions for half price, the company that can provide economically so as to effect the campaign "Artist", will have a commercial advertisement while projecting conceptual reflecting the message to be communicated at low cost. The money will be used to effect the campaign "artist" and to perform the cultural event that promotes.